2014
DOI: 10.1016/j.proeng.2014.12.248
|View full text |Cite
|
Sign up to set email alerts
|

A study on High Speed End Milling of Titanium Alloy

Abstract: Titanium alloys are widely used in aerospace industries, due to its high strength to weight ratio and light weight. This paper investigates high speed end milling of titanium alloy (Ti-6% Al-4% V) using carbide insert based end mill cutter. Effects of cutting forces during high speed machining of titanium alloys have got higher attention in selecting the optimal cutting conditions to improve the production and tool life. Due to Titanium alloy's low thermal conductivity, more heat concentration takes place on c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(31 citation statements)
references
References 6 publications
1
20
0
3
Order By: Relevance
“…It was also noticed that cutting force increased with higher cutting speed. This agrees with the assumption that more energy is required to remove a higher volume of material and hence higher cutting force [59,60], although this is in disagreement with the finding that higher cutting speeds may cause material softening, and hence lower cutting forces when machining steel alloys as described by Veiga et al [36]. Additionally, variations in nozzle positions/ angles and impinging distance had only a limited impact on cutting force.…”
Section: Process Analysis and Effect Of The New System (Part I)supporting
confidence: 66%
“…It was also noticed that cutting force increased with higher cutting speed. This agrees with the assumption that more energy is required to remove a higher volume of material and hence higher cutting force [59,60], although this is in disagreement with the finding that higher cutting speeds may cause material softening, and hence lower cutting forces when machining steel alloys as described by Veiga et al [36]. Additionally, variations in nozzle positions/ angles and impinging distance had only a limited impact on cutting force.…”
Section: Process Analysis and Effect Of The New System (Part I)supporting
confidence: 66%
“…Taguchi method and ANN found different sets of optimal combinations but the confirmation test revealed that both got almost same Ra values. V. Krishnaraj et.al [04] investigates high speed end milling of titanium alloy (Ti-6% Al-4% V) using carbide insert based end mill cutter. The experiments have been carried out under dry cutting conditions.…”
Section: Literature Surveymentioning
confidence: 99%
“…By observing from the test, the cutting force generated by upwards milling along the angle, the best surface quality, and the longest service life of the tool milling downwards along the angle could be obtained. Krishnaraj et al [14] detected that the cutting depth has maximum influence on the cutting force, while the cutting speed has a significant influence on temperature, after conducting a study on a high-speed TC4 cutting test using a carbide-tipped milling cutter. Liang et al [15] studied the tool wear and corresponding surface morphology in the processing of fine-grained tools machining TC4 at a high speed.…”
Section: Introductionmentioning
confidence: 99%